Orientation and the onset of neurological complications among brain injury and stroke patients. - Alverzo JP (Orientation & the Onset of Neurological Complications Among Brain Injury & Stroke Patients, 2004)
The relationship between the development of neurological complications and temporal disorientation among brain injury and stroke patients undergoing rehabilitation was explored in this descriptive study. Cognitive orientation is a construct of consciousness, and the Parallel Distributed Processing (PDP) model provided a framework for conceptualizing consciousness in this study. Data was collected by a retrospective chart review of a convenience sample of stroke and brain injury patients admitted to an acute rehabilitation hospital over a four month time frame. The dependent variable in the study was the Temporal Orientation Test (TOT) used as a daily measure of neurological status in the study hospital. Temporal orientation was defined as a score of 3 or less error points on the TOT for a period of 3 days or longer. A total of 167 patients were admitted during the time frame, and of those, 114 patients met the study criteria and were included in the data analysis. Based on the low incidence of neurological complications among the study patients, the independent variables were adjusted and defined as age, gender, years of education, number of co-morbidities, patient diagnosis, orientation status on admission, and use of narcotic/sedative medications. A logistical regression was performed using SPSS Release 11.01. Only one of the six variables, orientation status on admission, reliably predicted the onset of disorientation during the rehabilitation stay with an odds ratio of 0.217, p < .001. This indicates that the risk of becoming disoriented after a period of orientation during the rehabilitation stay increased by 78% among patients who are disoriented on admission to rehabilitation as compared to those who are oriented on admission. These findings confirm that temporal orientation is unstable during the period of rehabilitation following a brain injury or stroke.